Rain attenuation distribution characteristic of Ka band satellite communication - KANG Jian; WANG Yu-fei (Tongxin xuebao)
Using the ITU-R rain attenuation forecasting model,and based on the rainfall data and the geographic location parameters of main cities in our country,the isograms of rain attenuation distribution for the communication satellite with the orbital location 92° E in Ka band（30/20GHz）was presentd.A further analysis was made on the rain attenuation char-acteristic of the Ka band satellite communication system by integrating with the landform and the climate distribution pattern in our country.The results could be used as the theoretical basis when designing the Ka band satellite communica-tion system.